2015
DOI: 10.1086/680686
|View full text |Cite
|
Sign up to set email alerts
|

Women and Power: Unpopular, Unwilling, or Held Back?

Abstract: We use Spain's Equality Law to test for the existence of agency problems between party leaders and their constituents. The law mandates a 40 percent female quota on electoral lists in towns with populations above 5,000. Using pre-and postquota data by party and municipality, we implement a triple-difference design. We find that female quotas resulted in slightly better electoral results for the parties that were most affected by the quota. Our evidence shows that party leaders were not maximizing electoral res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(51 citation statements)
references
References 53 publications
5
46
0
Order By: Relevance
“…In Sweden, Besley et al (2013) find that party-based gender quotas have a positive effect on men's competence, mainly due to the replacement of mediocre male leaders with more competent men. Other studies have found a positive link between (both male and female) politicians' education levels and quota implementation (Baltrunaite et al 2014;Casas-Arce and Saiz 2011). Still others illustrate that women who are elected via quota laws are at least as efficient as legislators as their male peers, and even outpace men in some measures of competency (Catalano Weeks and Baldez 2014;Murray 2010).…”
Section: Acceleration Effects: Quotas Facilitating Women's Access To mentioning
confidence: 99%
“…In Sweden, Besley et al (2013) find that party-based gender quotas have a positive effect on men's competence, mainly due to the replacement of mediocre male leaders with more competent men. Other studies have found a positive link between (both male and female) politicians' education levels and quota implementation (Baltrunaite et al 2014;Casas-Arce and Saiz 2011). Still others illustrate that women who are elected via quota laws are at least as efficient as legislators as their male peers, and even outpace men in some measures of competency (Catalano Weeks and Baldez 2014;Murray 2010).…”
Section: Acceleration Effects: Quotas Facilitating Women's Access To mentioning
confidence: 99%
“…To overcome the problems of endogeneity and selection bias associated with OLS, we look at close elections and make use of a regression discontinuity design, or RDD (Imbens and Lemieux 2008;Hahn et al 2001;Lee and Card 2008;Brollo and Nannicini 2012;Pettersson-Lidbom 2008;Leigh 2008;Ferreira and Gyourko 2007;Folke 2014;Curto-Grau et al 2012;Casas-Arce and Saiz 2014). A RDD takes advantage of the fact that the probability of being a single-party majority government changes discontinuously at a certain cut-off point of the assignment variable.…”
Section: Identification and Forcing Variablementioning
confidence: 99%
“…For example, Esteve-Volart and Bagues (2012) suggest that a lack of political competition allows party organizations to recruit fewer women compared to what voters prefer. Then a gender quota might increase voter welfare if it is consistently implemented in all districts as indicated in Casas- Arce and Saiz (2015). Murray (2010) finds that women who entered parliament after France's quota law were as equally active and efficient as male lawmakers.…”
mentioning
confidence: 99%